Predicting strength outcomes for upper limb nerve transfer surgery in tetraplegia. (December 2022) - Stanley, Edward A.; Hill, Bridget; McKenzie, Dean P.; Chapuis, Pierre; Galea, Mary P.; van Zyl, Natasha
We report a retrospective study of 112 nerve transfers in 39 participants to investigate predictors of strength outcomes after nerve transfer surgery for upper limb reanimation in tetraplegia. We measured clinical and pre- and intraoperative neurophysiological assessment variables and compared them with strength outcomes 2 years after nerve transfer surgery. We found statistically significant improvement in Medical Research Council strength grades after nerve transfer surgery with lower cervical spine injuries (between one and two grades), lower donor nerve stimulation thresholds (half of a grade), greater motor evoked potential activity in recipient nerves (half of a grade) and greater muscle responses to intraoperative stimulation of donor (half of a grade) and recipient nerves (half of a grade). Level of evidence: III